A distributed heat transfer model for thermal-hydraulic analyses in sewer networks. (1st October 2021) - Figueroa, Alejandro; Hadengue, Bruno; Leitão, João P.; Rieckermann, Jörg; Blumensaat, Frank
Highlights: SWMM-HEAT estimates available heat budgets in sewer networks at high spatiotemporal resolution. SWMM-HEAT extends EPA-SWMM, and thus enables thermal-hydraulic simulations for existing models. Latent heat transfer should be considered in situations with high relative headspace humidity. The model is validated by two independent real-world case studies of different scale. Source code, a specific model implementation and field data are available on Github. Abstract: Thermal-hydraulic considerations in urban drainage networks are essential to utilise available heat capacities from waste- and stormwater. However, available models are either too detailed or too coarse; fully coupled thermal-hydrodynamic modelling tools are lacking. To predict efficiently water-energy dynamics across an entire urban drainage network, we suggest the SWMM-HEAT model, which extends the EPA-StormWater Management Model with a heat-balance component. This enables conducting more advanced thermal-hydrodynamic simulation at full network scale than currently possible. We demonstrate the usefulness of the approach by predicting temperature dynamics in two independent real-world cases under dry weather conditions. We furthermore screen the sensitivity of the model parameters to guide the choice of suitable parameters in future studies. Comparison with measurements suggest that the model predicts temperature dynamics adequately, with RSR values ranging between 0.71 and 1.1. The results of our study show that modelled in-sewer wastewater temperatures are particularly sensitive to soil and headspace temperature, and headspace humidity. Simulation runs are generally fast; a five-day period simulation at high temporal resolution of a network with 415 nodes during dry weather was completed in a few minutes. Future work should assess the performance of the model for different applications and perform a more comprehensive sensitivity analysis under more scenarios. To facilitate the efficient estimation of available heat budgets in sewer networks and the integration into urban planning, the SWMM-HEAT code is made publicly available. Graphical abstract: Image, graphical abstract